Corruption and Fertility: Evidence from OECD countries - Eiji Yamamura (Economics and Econometrics Research Institute (EERI), 2011)
This paper uses panel data of OECD countries during the period 1995–2003 to examine how corruption affects fertility. The Corruption Perceptions Index is used to measure the degree of corruption. Fixed effects IV estimation and the Arellano-Bond dynamic panel estimation are employed to control for endogenous bias and unobservable country-specific effects. Results suggest that the fertility rate is higher in less corrupted countries. From this, the argument can be made that lack of political corruption underlies desirable conditions for child rearing in developed countries.
Keywords: D73; J13; 330; Corruption; fertility; political institutions